2023
DOI: 10.3389/fimmu.2023.1282016
|View full text |Cite
|
Sign up to set email alerts
|

Non-glycosylated G protein with CpG ODN provides robust protection against respiratory syncytial virus without inducing eosinophilia

Eigo Kawahara,
Takehiko Shibata,
Toshiro Hirai
et al.

Abstract: IntroductionRespiratory syncytial virus (RSV) vaccines targeting the fusion glycoprotein (F protein) are highly effective clinically in preventing RSV challenges. The attachment glycoprotein (G protein) is a potentially effective vaccine antigen candidate, as it is important for cell adhesion during infection. However, vaccine-associated enhanced diseases in mice, such as eosinophilic lung inflammation following RSV challenge, are a concern with G protein vaccines. This study aimed to design an effective G pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Finally, the G protein produced in this study was not glycosylated due to the use of the E. coli expression system, making it difficult to compare what would actually happen in vivo. Nevertheless, Kawahara et al reported that non-glycosylated G protein provided robust protection against RSV, as shown by the modest correlation with neutralizing activities in this study, particularly in children and adolescents ( Figure 4 ) [ 19 ].…”
Section: Discussionmentioning
confidence: 60%
“…Finally, the G protein produced in this study was not glycosylated due to the use of the E. coli expression system, making it difficult to compare what would actually happen in vivo. Nevertheless, Kawahara et al reported that non-glycosylated G protein provided robust protection against RSV, as shown by the modest correlation with neutralizing activities in this study, particularly in children and adolescents ( Figure 4 ) [ 19 ].…”
Section: Discussionmentioning
confidence: 60%
“…The realization that the efficacy of viral vaccines does not necessarily depend on a strong response against the fusion protein was recognized for both influenza, where vaccine efficacy declined when the neuraminidase content was low [ 15 ], and for the paramyxovirus Hendra virus, for which an efficacious vaccine is approved based solely on the attachment protein H [ 16 , 17 ]. Although the G protein has been undervalued compared to F, the recent demonstration of strong neutralization in hAEC cultures of antibodies against G show the potential as a vaccine component [ 5 , 18 , 19 , 20 ], and protection from RSV challenge was demonstrated in mice after immunization with G [ 21 , 22 , 23 , 24 , 25 ]. Therefore, if durability and breadth of immunity elicited by current F-based RSV vaccines may turn out to be insufficient, inclusion of an additional RSV vaccine component based on the attachment protein G might increase the chance of durable and broad protection.…”
Section: Introductionmentioning
confidence: 99%